A Survey of Government Regulation and Intervention in Financial Markets - Klapper, Leora; Zaidi, Rida (World Bank, Washington, DC, 2012)
There has been renewed focus on financial systems, especially in the light of recent literature that documents a positive and robust relationship between development of financial systems and economic growth. Irrespective of how financial development is measured, there is a clear causal relationship with per capita income. King and Levine (1993) was the first paper that examined economic growth for a dataset that spans from 1960-1989 and found predictive power of financial systems in growth. Another richer dataset from 1960-1995 reinforces the existing relationship between finance and growth, while taking into account the issue of reverse causality (Levine, Loayza and Beck 2000). The idea of reverse causality is that it is also possible that economic growth may encourage development of financial systems and these results may reflect reverse feedback rather than any effect of finance on growth. The authors use the recent discovery that systems with English common law tend to have deeper financial systems, to employ legal origins as an effective instrument. Their results rule out the thesis that the relationship between finance and growth is driven by reverse causality. The policy prescription the authors provide is that developing countries should not attempt to engineer credit expansion and financial system development. Instead they should create an environment conducive for participation of individuals in the market system, for financial system to deliver services effectively and functions most required by an economy are provided by finance (World Bank 2001). Any policies where government actively seeks to influence financial market outcomes are likely to have adverse effects. The ensuing discussion in this report highlights the pervasive negative influence of the government in finance, in most emerging economies. It underscores and points out cases of efficiently performing financial systems in countries where government has limited its involvement to developing a sound business environment.